2018
DOI: 10.1016/j.jiac.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of urinary tract infections and antimicrobial resistance in hospitalized urology patients in Asia: 10-Year results of the Global Prevalence Study of Infections in Urology (GPIU)

Abstract: Uropathogens in many Asian countries had high resistance to broad-spectrum antibiotics. Knowledge of regional and local resistance data and prudent use of antibiotics are important for proper management of UTI in Asian countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 38 publications
(39 reference statements)
4
26
0
1
Order By: Relevance
“…Similar observations were reported in the urine samples, globally. [15][16][17][18][19][20] Urinary tract infections are believed to be the second most predominant communitybased and nosocomial infections, worldwide. 21,22 These findings represent that urine and urinary tract environment demonstrate a higher prevalence of uropathogens due to the longer hospital stay, sexual activity, diabetes, hormonal imbalance, and genetic susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were reported in the urine samples, globally. [15][16][17][18][19][20] Urinary tract infections are believed to be the second most predominant communitybased and nosocomial infections, worldwide. 21,22 These findings represent that urine and urinary tract environment demonstrate a higher prevalence of uropathogens due to the longer hospital stay, sexual activity, diabetes, hormonal imbalance, and genetic susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…The Infectious Diseases Society of America suggest a threshold of 20% as the resistance prevalence at which the agent is no longer recommended for empirical treatment of acute cystitis; this may no longer be feasible in the Asia-Pacific region, where Gram-negative resistance is escalating rapidly [1,5,6]. In fact, our study showed that carbapenems and amikacin were the only antibiotics with susceptibilities above 80%.…”
Section: Discussionmentioning
confidence: 72%
“…Ceftriaxone is currently one of the antibiotics recommended for the empiric treatment of UTI in the Asia-Pacific region [4]. However, cephalosporin and fluoroquinolone resistance are on the rise in the Asia-Pacific region [2,5,6]. This has led to concerns about the risks of the widespread use of empiric ceftriaxone therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Based on literature studies in 90% of urinary system infections in diabetic patients pathogenic agent is E. coli 17 . Antibiotic resistance of uropathogens involving in community-acquired and nosocomial urinary system infections is gradually increasing 18,19 . The increase in bacterial resistance rates may be due to the empirically medical prescription, individual self-medication or a low adherence to treatment, inefficient hospital infection control services and poor hygiene.…”
Section: Discussionmentioning
confidence: 99%